Fluorine-doped graphite material as well as preparation method and application thereof

By mixing graphite powder and fluorine source powder at a specific mass ratio and heat-treated, fluorine-doped graphite materials are prepared, which solves the problems of high cost and complex process of existing graphite fluorination methods, and achieves efficient modification of graphite negative electrode materials, which is suitable for low-cost and high-mass production of industrial production.

CN119683617AActive Publication Date: 2025-03-25SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411875525.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing graphite fluorination methods are costly and complex in processes, making them difficult to be suitable for low-cost and high-mass production industrial production.

Method used

Fluorine-doped graphite material is prepared by mixing graphite powder with fluorine source powder in a specific mass ratio and heat treatment at 300~800°C. The process is simple and low in cost, and the prepared materials have good electrochemical properties.

Benefits of technology

This method significantly improves the first Coulomb efficiency, cycle stability and rate performance of graphite negative electrode materials, reduces internal resistance and charge transfer resistance, and is suitable for low-cost and high-mass production industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683617A_ABST
    Figure CN119683617A_ABST
Patent Text Reader

Abstract

The invention discloses a fluorine-doped graphite material and a preparation method and application thereof, and the preparation method of the fluorine-doped graphite material comprises the following steps: mixing graphite powder with fluorine source powder to obtain a primary material; the mass ratio of the graphite powder to the fluorine source powder is (1-20): 1; and carrying out heat treatment on the primary material at 300-800 DEG C to obtain the fluorine-doped graphite material. The graphite negative electrode material prepared by using a solid phase fluorination method is obviously superior to non-fluorinated graphite in the aspects of initial coulombic efficiency, cycling stability and rate capability. Therefore, the solid-phase fluorination method is an effective and practical graphite negative electrode material modification method and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fluorine-doped graphite material and a preparation method and application thereof. Background Art

[0002] As a negative electrode material for lithium-ion batteries, graphite is widely used because of its high theoretical specific capacity, good cycle stability and low cost. However, graphite has a large irreversible capacity loss during the first charge and discharge process, and its performance degrades during high-rate charge and discharge. In order to solve these problems, researchers have tried to modify graphite by various methods, among which fluorination is an effective means. Fluorination can improve the surface properties of graphite, improve the first coulomb efficiency, and enhance the cycle stability and rate performance. Patent CN117855441A discloses a fluorine-doped graphite negative electrode material, which is sintered by a fluorine source organic compound and an amine organic compound, and can further improve the fast charging performance of lithium-ion batteries while improving the energy density and cycle performance of lithium-ion batteries. However, the method uses high raw material costs of organic fluorides and amine compounds, requires precise control equipment and reaction devices to ensure accurate control of reaction conditions, and increases equipment investment. Therefore, a lower-cost fluorine doping method is needed to be suitable for low-cost, high-volume industrial production. Summary of the invention

[0003] The purpose of the present invention is to solve the problems of high cost and complicated process of existing graphite fluorination methods, and to provide a fluorine-doped graphite material and its preparation method and application. The method of the present invention has simple process and low cost, and the prepared fluorine-doped graphite negative electrode material has good electrochemical properties.

[0004] The present invention solves the above technical problems through the following technical solutions:

[0005] The present invention provides a method for preparing a fluorine-doped graphite material, which comprises the following steps:

[0006] Mixing graphite powder and fluorine source powder to obtain a preliminary material; the mass ratio of the graphite powder to the fluorine source powder is (1-20):1;

[0007] The preliminary material is heat treated at 300-800° C. to obtain a fluorine-doped graphite material.

[0008] In the present invention, the mixing is preferably carried out by ball milling, which is conventional in the art.

[0009] In some of the schemes, the rotation speed of the ball mill is 200-500 r / min, such as 300 r / min, 350 r / min or 400 r / min.

[0010] In some of the schemes, the ball milling time is 10 to 25 hours, for example, 10 hours, 12 hours, 18 hours, 20 hours, 24 hours and 30 hours.

[0011] In some of the schemes, the ball-to-material ratio of the ball mill is (10-20):1, such as 15:1 or 20:1.

[0012] In some embodiments, the grinding bodies of the ball mill are stainless steel balls or ceramic balls.

[0013] In some of the schemes, the mass ratio of the graphite powder to the fluorine source powder is (2-10):1, preferably (2-3):1, for example, 2:1, 2.5:1, 3.3:1, 5:1 or 10:1.

[0014] When the mass ratio of graphite powder to fluorine source powder is too low (such as 1:43), the degree of fluorination is very high, which will lead to over-fluorination, unstable structure, low initial coulomb efficiency; the material structure is too loose, the cycle stability is poor; the conductivity of the material decreases, and the rate performance is poor. If the mass ratio of graphite powder to fluorine source powder is too high (such as 100:1), it will lead to low degree of fluorination and incomplete fluorination; large irreversible capacity loss and low initial coulomb efficiency; due to insufficient fluorination, the volume expansion of the material during charging and discharging is large, and the cycle stability is poor; the diffusion rate of lithium ions is low, and the rate performance is poor; the internal resistance and charge transfer resistance are high. Therefore, the mass ratio range of the present invention is preferred.

[0015] In some of the schemes, the fluorine source powder is an inorganic fluorine source, preferably, the inorganic fluorine source is KF, CaF2, NH4F or K2MnF6, preferably KF, CaF2, NH4F.

[0016] In some of the embodiments, the D50 particle size of the fluorine source powder is 5 to 20 μm, for example, 7.9 μm, 10.1 μm, 12 μm, 12.3 μm, 13.9 μm, 14.7 μm, 15.3 μm or 15.7 μm.

[0017] In some of the schemes, the graphite powder is natural graphite powder or artificial graphite powder.

[0018] In some of the schemes, the D50 particle size of the graphite powder is 5-20 μm, for example, 5.1 μm, 6.5 μm, 7.4 μm, 8 μm, 8.4 μm, 9.2 μm or 10.3 μm; preferably, the standard deviation (SD) of the particle size distribution of the graphite powder is less than 3 μm.

[0019] The appropriate graphite particle size gives the graphite a larger specific surface area and is beneficial to improving the degree and uniformity of fluorination. If the particle size is too large, the fluorination reaction will be uneven, resulting in poor performance consistency of the fluorinated graphite. Although a graphite particle size that is too small (such as 2~5μm) can improve the initial coulombic efficiency and rate performance to a certain extent, it will lead to a decrease in cycle stability and increase the complexity of the graphite processing process.

[0020] In some embodiments, the graphite powder has a crystallinity greater than 95%, such as 96.3%.

[0021] In some embodiments, the purity of the graphite powder is greater than 99.9%.

[0022] In some of the schemes, the temperature of the heat treatment is 500-700°C, preferably 700°C, for example 300°C, 400°C, 500°C, 600°C, 700°C or 800°C.

[0023] In some of the schemes, the heat treatment time is 1 to 10 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours and 6 hours.

[0024] In some embodiments, the heat treatment is performed in an inert atmosphere, preferably, the inert atmosphere is argon or nitrogen.

[0025] In some of the schemes, the heat treatment equipment is conventional in the art, such as a muffle furnace or a tube furnace.

[0026] In some embodiments, the heat treatment further comprises cooling, washing and drying steps.

[0027] The steps of cooling, washing and drying are conventional in the art.

[0028] In some embodiments, the cooling step includes: naturally cooling to room temperature.

[0029] Here, "room temperature" refers to 10~30℃.

[0030] In some of the schemes, the washing is performed with deionized water or ethanol to remove unreacted fluorine source and other impurities. Preferably, the washing is performed 2 to 5 times;

[0031] In some of the schemes, the drying temperature is 60-100°C, for example, 60°C, 70°C, 80°C and 90°C; preferably, the drying time is 10-25h, for example, 10h, 12h, 16h, 20h and 24h.

[0032] The present invention also provides a fluorine-doped graphite material prepared by the above-mentioned method for preparing the fluorine-doped graphite material.

[0033] The fluorine-doped graphite material of the present invention is a layered compound, in which fluorine atoms are embedded between graphite layers. After fluorination, the interlayer spacing of graphite increases, and the typical interlayer spacing increases from 0.335 nm of unfluorinated graphite to about 0.35-0.40 nm of fluorinated graphite.

[0034] The present invention also provides an application of the above fluorine-doped graphite material as a negative electrode material in a lithium-ion battery.

[0035] The positive and progressive effects of the present invention are:

[0036] (1) The graphite anode material prepared by solid-phase fluorination is significantly better than that of unfluorinated graphite in terms of first coulombic efficiency, cycle stability and rate performance. This shows that solid-phase fluorination is an effective and practical method for modifying graphite anode materials and has broad application prospects.

[0037] (2) The fluorination treatment significantly increased the specific capacity of the graphite negative electrode material. The discharge capacity of all examples at each rate was higher than that of the non-fluorinated comparative example 1, which indicates that the fluorination treatment can effectively increase the amount of lithium ion embedded in the material and improve the lithium storage capacity of the material.

[0038] The fluorination treatment significantly improves the rate performance of the graphite negative electrode material, especially at high rates (2C and 5C), the discharge capacity of the embodiment is significantly higher than that of the comparative example 1. This shows that the fluorination treatment can improve the conductivity of the material and the diffusion rate of lithium ions, and improve the performance of the material under high rate charge and discharge conditions;

[0039] Fluorination treatment improves the first coulombic efficiency of the material and reduces the irreversible capacity loss, which is particularly evident at low rates (0.1C and 0.5C). This indicates that fluorination treatment can improve the surface properties of the material, reduce side reactions, and improve the electrochemical stability of the material.

[0040] (3) The fluorination treatment significantly reduced the internal resistance of the graphite negative electrode material. The DCIR of all examples was lower than that of the unfluorinated comparative example 1, which indicates that the fluorination treatment can effectively improve the conductivity of the material and reduce the energy loss inside the battery.

[0041] Fluorination treatment significantly reduces the charge transfer resistance, increases the electrochemical reaction activity of the material, improves the conductivity of the material, reduces the solution resistance, reduces the diffusion resistance of lithium ions in the material, and increases the diffusion rate of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the SEM image of graphite fluoride. DETAILED DESCRIPTION

[0043] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0044] The graphite powder in the following examples and comparative examples has a crystallinity of 96.3% and a purity of 99.96%.

[0045] Example 1

[0046] (1) Weigh 10 g of natural graphite powder (D50 particle size: 6.5 μm) and 5 g of KF (D50 particle size: 15.3 μm).

[0047] (2) Put graphite powder and KF into a ball mill, add an appropriate amount of stainless steel balls, and the ball-to-material ratio is 15:1. Ball mill the graphite powder and KF in a ball mill for 24 hours at a speed of 300 r / min.

[0048] (3) The mixed powder was evenly spread in a crucible, placed in a muffle furnace, and heat treated at 500 °C for 4 h in an argon atmosphere.

[0049] (4) After naturally cooling to room temperature, the resulting mixture was washed with deionized water three times and then dried at 80 °C for 12 h to obtain graphite fluoride.

[0050] Example 2

[0051] (1) Weigh 10 g of artificial graphite (D50 particle size: 10.3 μm) and 3 g of CaF2 (D50 particle size: 12 μm).

[0052] (2) Put graphite powder and CaF2 into a ball mill, add an appropriate amount of ceramic balls, with a ball-to-material ratio of 15:1, and ball mill for 12 hours at a ball mill speed of 300 r / min.

[0053] (3) The mixed powder was evenly spread in a crucible, placed in a tube furnace, and heat treated at 600 °C for 3 h in a nitrogen atmosphere.

[0054] (4) After naturally cooling to room temperature, the mixture was washed with ethanol three times and then dried at 60 °C for 24 h to obtain graphite fluoride.

[0055] Example 3

[0056] (1) Weigh 10 g of natural graphite powder (D50 particle size: 7.4 μm) and 2 g of NH4F (D50 particle size: 13.9 μm).

[0057] (2) Put graphite powder and NH4F into a ball mill, add an appropriate amount of stainless steel balls, with a ball-to-material ratio of 15:1, and ball mill for 18 hours at a ball mill speed of 350 r / min.

[0058] (3) The mixed powder was evenly spread in a crucible, placed in a muffle furnace, and heat treated at 400 °C for 5 h in an argon atmosphere.

[0059] (4) After naturally cooling to room temperature, the resulting mixture was washed with deionized water three times and then dried at 70 °C for 16 h to obtain graphite fluoride.

[0060] Example 4

[0061] (1) Weigh 10 g of artificial graphite powder (D50 particle size: 9.2 μm) and 4 g of KF (D50 particle size: 7.9 μm).

[0062] (2) Put graphite powder and KF into a ball mill, add an appropriate amount of ceramic balls, and the ball-to-material ratio is 20:1. Ball mill the graphite powder and KF in a ball mill for 30 hours at a ball mill speed of 350 r / min.

[0063] (3) The mixed powder was evenly spread in a crucible, placed in a tube furnace, and heat treated at 700 °C for 2 h in a nitrogen atmosphere.

[0064] (4) After naturally cooling to room temperature, the mixture was washed with ethanol three times and then dried at 90 °C for 10 hours to obtain graphite fluoride.

[0065] Example 5

[0066] (1) Weigh 10 g of natural graphite powder (D50 particle size: 5.1 μm) and 1 g of CaF2 (D50 particle size: 12.3 μm).

[0067] (2) Put graphite powder and CaF2 into a ball mill, add an appropriate amount of stainless steel balls, with a ball-to-material ratio of 20:1, and ball mill for 10 hours at a ball mill speed of 400 r / min.

[0068] (3) The mixed powder was evenly spread in a crucible, placed in a muffle furnace, and heat treated at 300°C for 6 hours in an argon atmosphere.

[0069] (4) After naturally cooling to room temperature, the resulting mixture was washed with deionized water three times and then dried at 60 °C for 20 h to obtain graphite fluoride.

[0070] Example 6

[0071] (1) Weigh 10 g of artificial graphite powder (D50 particle size: 8.4 μm) and 5 g of NH4F (D50 particle size: 10.1 μm).

[0072] (2) Put graphite powder and KF into a ball mill, add an appropriate amount of ceramic balls, and the ball-to-material ratio is 20:1. Ball mill the graphite powder and KF in a ball mill for 20 hours at a ball mill speed of 400 r / min.

[0073] (3) The mixed powder was evenly spread in a crucible, placed in a tube furnace, and heat treated at 800°C for 1 hour in a nitrogen atmosphere.

[0074] (4) After naturally cooling to room temperature, the mixture was washed with ethanol three times and then dried at 80 °C for 12 h to obtain graphite fluoride.

[0075] Example 7

[0076] (1) Weigh 10 g of natural graphite powder (D50 particle size: 8 μm) and 5 g of KF (D50 particle size: 14.7 μm).

[0077] (2) Place graphite powder and KF in a container and mix briefly using a manual stirrer to ensure that the two are initially mixed evenly.

[0078] (3) The mixed powder was evenly spread in a crucible, placed in a muffle furnace, and heat treated at 500°C for 4 h in an argon atmosphere.

[0079] (4) Cool naturally to room temperature, wash with deionized water three times, and then dry at 80°C for 12 hours to obtain graphite fluoride.

[0080] Example 8

[0081] (1) Weigh 10 g of natural graphite powder (D50 particle size: 8 μm) and 5 g of K2MnF6 (D50 particle size: 15.7 μm).

[0082] (2) Put graphite powder and K2MnF6 into a ball mill, add an appropriate amount of stainless steel balls, and the ball-to-material ratio is 15:1. Ball mill the graphite powder and K2MnF6 for 24 hours at a ball mill speed of 300 r / min.

[0083] (3) The ball-milled powder was evenly spread in a crucible, placed in a muffle furnace, and heat treated at 500°C for 4 h in an argon atmosphere.

[0084] (4) Cool naturally to room temperature, wash with deionized water three times, and then dry at 80°C for 12 hours to obtain graphite fluoride.

[0085] Comparative Example 1

[0086] (1) Weigh 10 g of natural graphite powder (D50 particle size: 8.5 μm) without adding any fluorine source.

[0087] (2) Put graphite powder into a ball mill and add an appropriate amount of stainless steel balls with a ball-to-material ratio of 15:1. Mill the graphite powder in a ball mill for 24 hours at a speed of 200 r / min.

[0088] (3) The ball-milled powder was evenly spread in a crucible, placed in a muffle furnace, and heat treated at 500°C for 4 h in an argon atmosphere.

[0089] (4) After naturally cooling to room temperature, the mixture was washed with deionized water three times and then dried at 80 °C for 12 h to obtain unfluorinated graphite.

[0090] Effect Example

[0091] The graphite obtained in the above embodiments and comparative examples is used to prepare electrodes and assemble into batteries. The preparation method of the battery is as follows:

[0092] 1. Negative electrode preparation

[0093] (1) Material preparation

[0094] Conductive agent: Super P or acetylene black, 5-10 wt%.

[0095] Binder: polyvinylidene fluoride (PVDF), 5-10 wt%.

[0096] Solvent: N-methylpyrrolidone (NMP).

[0097] (2) Mix the fluorinated graphite, conductive agent and binder prepared in the above embodiment in proportion, add an appropriate amount of NMP, and stir at room temperature for 3-4 hours using a stirrer until a uniform slurry is formed. Use a scraper method to evenly coat the slurry on the copper foil with a thickness of 80-100 μm. Dry at 60-80°C for 2-4 hours, and then vacuum dry at 120-150°C for 12 hours. Press the dried electrode sheet with a roller press at a pressure of 10-20 MPa to increase the density and mechanical strength of the electrode. Cut the pressed electrode sheet into the required size for later use.

[0098] 2. Cathode preparation

[0099] (1) Material preparation:

[0100] Lithium cobalt oxide (LiCoO2) or other commercial cathode materials.

[0101] Conductive agent: Super P or acetylene black, 5-10 wt%.

[0102] Binder: polyvinylidene fluoride (PVDF), 5-10 wt%.

[0103] Solvent: N-methylpyrrolidone (NMP).

[0104] (2) Mix the positive electrode active material, conductive agent and binder in proportion, add an appropriate amount of NMP, and use a mixer to stir at room temperature for 3-4 hours until a uniform slurry is formed. Use a scraper method to evenly coat the slurry on the aluminum foil with a thickness of 80-100μm. Dry at 60-80°C for 2-4 hours, and then vacuum dry at 120-150°C for 12 hours. Press the dried electrode sheet with a roller press at a pressure of 10-20 MPa to increase the density and mechanical strength of the electrode. Cut the pressed electrode sheet into the required size and set aside.

[0105] 3. Battery assembly

[0106] Select a suitable diaphragm, such as polypropylene (PP) or polyethylene (PE) diaphragm, lithium-ion battery electrolyte, and battery shell, such as CR2032 button battery shell. Place the positive electrode, diaphragm, and negative electrode into the battery shell in sequence, inject an appropriate amount of electrolyte, and seal the battery.

[0107] 4. Electrochemical performance test method

[0108] (1) Discharge capacity

[0109] Test conditions: Charge and discharge voltage range: 0.01-2.0 V (relative to Li / Li⁺).

[0110] Current density: 0.1 C

[0111] Test temperature: 25℃

[0112] Test steps: Use constant current charge and discharge equipment to perform charge and discharge tests. Record the discharge curve and calculate the discharge capacity.

[0113] (2) First Coulombic efficiency (first efficiency)

[0114] Test conditions: Charge and discharge voltage range: 0.01-2.0 V (relative to Li / Li⁺).

[0115] Current density: 0.1 C.

[0116] Test temperature: 25℃.

[0117] Test steps: Perform a complete charge and discharge cycle.

[0118] (3) 1000-cycle capacity retention rate

[0119] Test conditions: Charge and discharge voltage range: 0.01-2.0 V (relative to Li / Li⁺).

[0120] Current density: 0.1 C.

[0121] Test temperature: 25℃.

[0122] Test steps: Perform 1000 charge and discharge cycles and calculate the 1000-cycle capacity retention rate.

[0123] (4) Rate performance

[0124] Test conditions: Charge and discharge voltage range: 0.01-2.0 V (relative to Li / Li⁺).

[0125] Current density: 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C.

[0126] Test temperature: 25℃.

[0127] Test steps: Carry out charge and discharge tests at different current densities. Record the discharge capacity at different current densities.

[0128] (5) DC internal resistance (DCIR)

[0129] Test conditions: Charge and discharge voltage range: 0.01-2.0 V (relative to Li / Li⁺).

[0130] Current density: 0.1 C.

[0131] Test temperature: 25℃.

[0132] Test steps: Use a DC internal resistance tester to test. Apply a small current pulse (such as 10 mA) and record the voltage change.

[0133] (6) Electrochemical impedance spectroscopy (EIS)

[0134] Test conditions: Test frequency range: 1MHz - 0.01Hz.

[0135] AC disturbance amplitude: 10 mV.

[0136] Test temperature: 25℃.

[0137] Test steps: Use an electrochemical workstation to perform EIS test. Record the impedance spectrum. Analyze the various impedance components in the impedance spectrum, such as ohmic resistance, charge transfer resistance, and diffusion resistance.

[0138] 5. Standard test methods

[0139] Discharge capacity, first efficiency, 1000-cycle capacity retention rate, rate performance: refer to the International Electrotechnical Commission (IEC) standards, such as IEC 61960-3:2017 "Portable secondary lithium batteries and battery packs Part 3: Safety requirements".

[0140] DC internal resistance (DCIR): Please refer to the relevant test methods in IEC 61960-3:2017.

[0141] Electrochemical impedance spectroscopy (EIS): Please refer to ASTM E1065-17 "Standard Guide for Electrochemical Impedance Spectroscopy Measurements".

[0142] The test results are shown in Tables 1 to 3.

[0143] Table 1 Capacity and initial efficiency test results of the embodiments and comparative examples

[0144]

[0145] Table 2 The test results of the embodiment and the comparative example

[0146]

[0147] Table 3 DCIR and EIS test results of the embodiments and comparative examples

[0148]

[0149] It can be seen that the graphite anode material prepared by solid phase fluorination is significantly better than the unfluorinated graphite in terms of first coulombic efficiency, cycle stability and rate performance. This shows that solid phase fluorination is an effective and practical method for modifying graphite anode materials and has broad application prospects.

[0150] The fluorination treatment significantly increased the specific capacity of the graphite negative electrode material, and the discharge capacity of all examples at each rate was higher than that of the non-fluorinated comparative example 1. This shows that the fluorination treatment can effectively increase the amount of lithium ion embedded in the material and improve the lithium storage capacity of the material.

[0151] The fluorination treatment significantly improves the rate performance of the graphite negative electrode material, especially at high rates (2C and 5C), the discharge capacity of the embodiment is significantly higher than that of the comparative example 1. This shows that the fluorination treatment can improve the conductivity of the material and the diffusion rate of lithium ions, and improve the performance of the material under high rate charge and discharge conditions.

[0152] The fluorination treatment improves the first coulombic efficiency of the material and reduces the irreversible capacity loss, which is particularly evident at low rates (0.1C and 0.5C). This shows that the fluorination treatment can improve the surface properties of the material, reduce side reactions, and improve the electrochemical stability of the material.

[0153] The fluorination treatment significantly reduced the internal resistance of the graphite negative electrode material, and the DCIR of all examples was lower than that of the non-fluorinated comparative example 1. This shows that the fluorination treatment can effectively improve the conductivity of the material and reduce the energy loss inside the battery.

[0154] Fluorination treatment significantly reduces the charge transfer resistance and improves the electrochemical reaction activity of the material. It improves the conductivity of the material and reduces the solution resistance. It reduces the diffusion resistance of lithium ions in the material and increases the diffusion rate of lithium ions.

Claims

1. A method for preparing a fluorine-doped graphite material, characterized in that: It includes the following steps: Mixing graphite powder and fluorine source powder to obtain a preliminary material; the mass ratio of the graphite powder to the fluorine source powder is (1-20):1; The preliminary material is heat treated at 300-800° C. to obtain a fluorine-doped graphite material.

2. The method for preparing fluorine-doped graphite material according to claim 1, characterized in that: The mixing is carried out by ball milling; Preferably, the ball milling satisfies one or more of the following conditions: ① The rotation speed of the ball mill is 200-500 r / min, for example, 300 r / min, 350 r / min or 400 r / min; ② The ball milling time is 10 to 25 hours, such as 10 hours, 12 hours, 18 hours, 20 hours, 24 hours and 30 hours; ③ The ball-to-material ratio of the ball mill is (10-20):1, for example 15:1 or 20:

1.

3. The method for preparing fluorine-doped graphite material according to claim 1, characterized in that: The mass ratio of the graphite powder to the fluorine source powder is (2-10):1, preferably (2-3):1, such as 2:1, 2.5:1, 3.3:1, 5:1 or 10:

1.

4. The method for preparing fluorine-doped graphite material according to claim 1, characterized in that: The fluorine source powder meets one or more of the following conditions: ① The fluorine source powder is an inorganic fluorine source, preferably, the inorganic fluorine source is KF, CaF2, NH4F or K2MnF6; ② The D50 particle size of the fluorine source powder is 5-20 μm, for example, 7.9 μm, 10.1 μm, 12 μm, 12.3 μm, 13.9 μm, 14.7 μm, 15.3 μm or 15.7 μm.

5. The method for preparing fluorine-doped graphite material according to claim 1, characterized in that: The graphite powder meets one or more of the following conditions: ① The graphite powder is natural graphite powder or manufactured graphite powder; ② The D50 particle size of the graphite powder is 5 to 20 μm, for example, 5.1 μm, 6.5 μm, 7.4 μm, 8 μm, 8.4 μm, 9.2 μm or 10.3 μm; preferably, the standard deviation of the particle size distribution of the graphite powder is less than 3 μm; ③ The crystallinity of the graphite powder is greater than 95%, for example 96.3%; ④ The purity of the graphite powder is greater than 99.9%.

6. The method for preparing fluorine-doped graphite material according to claim 1, characterized in that: The heat treatment satisfies one or more of the following conditions: ① The temperature of the heat treatment is 500-700°C, preferably 700°C, for example 300°C, 400°C, 500°C, 600°C, 700°C or 800°C; ② The heat treatment time is 1 to 10 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours and 6 hours; ③ The heat treatment is carried out in an inert atmosphere, preferably, the inert atmosphere is argon or nitrogen.

7. The method for preparing fluorine-doped graphite material according to claim 1, characterized in that: After the heat treatment, the steps of cooling, washing and drying are also included.

8. The method for preparing fluorine-doped graphite material according to claim 7, characterized in that: The preparation method of the fluorine-doped graphite material meets one or more of the following conditions: ① The cooling step includes: naturally cooling to room temperature; ② The washing is performed with deionized water or ethanol, preferably, the washing is performed 2 to 5 times; ③ The drying temperature is 60-100°C, such as 60°C, 70°C, 80°C and 90°C; preferably, the drying time is 10-25h.

9. A fluorine-doped graphite material prepared by the method for preparing a fluorine-doped graphite material according to any one of claims 1 to 8.

10. Use of the fluorine-doped graphite material as claimed in claim 9 as a negative electrode material in a lithium-ion battery.

Citation Information

Patent Citations

  • Preparation method for graphene fluoride colloidal material

    CN104627975A

  • Carbon fluoride material as well as preparation method and application thereof

    CN111326735A

  • Novel graphite fluoride composite lithium ion battery negative electrode material and preparation method thereof

    CN111628168A

  • Fluoride surface modified secondary battery carbon negative electrode material and preparation method thereof

    CN112786862A

  • Fluorine-doped graphite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

    CN117855441A